The influence of water–rock interactions on household well water in an area of high prevalence chronic kidney disease of unknown aetiology (CKDu) - Liza K. McDonough (Nature Portfolio, 2021)
Abstract Poor drinking water quality in household wells is hypothesised as being a potential contributor to the high prevalence of chronic kidney disease of uncertain aetiology (CKDu) among the farming communities of the Medawachchiya area, Anuradhapura, Sri Lanka. One of the natural processes that can affect water quality is the dissolution of minerals contained within an aquifer by water–rock interactions (WRIs). Here we present a comprehensive assessment of WRIs and their influence on the water chemistry in household wells and spring waters in the Medawachchiya area by combining measurements of environmental isotopes, such as strontium, lithium and stable carbon isotopes and inorganic chemistry parameters, and modelling geochemical mass balance reactions between rainfall and groundwater samples. Our results reveal the presence of strontium, dissolved from both silicate and carbonate minerals, with high isotopic (87Sr/86Sr) ratios of up to 0.7316. Geochemical mass balance modelling and prior 87Sr/86Sr studies on the Wanni Complex bedrock suggest these strontium values may be the result of biotite dissolution. We also identify lithium and uranium contributed from the dissolution of silicates, albeit at concentrations too low to constitute a known health risk. In contrast, the levels of magnesium and calcium in our samples are high and demonstrate that, despite the felsic bedrock, well water chemistry in the Medawachchiya area is dominated by carbonate dissolution.